Corporate `excesses' and financial market dynamics - Angela Maddaloni; Darren Pain (European Central Bank (ECB), 2004)
The recent corporate failures in the US and in Europe have considerably damaged investors' confidence in the functioning of financial markets and the ability of the regulatory framework to safeguard their interest and prevent fraud. These episodes demonstrate that market failures exist, which can undermine the effectiveness of market discipline to ensure the appropriate allocation of capital. Specifically the paper considers four particular features of financial markets that may have given rise to market failures: (a) perverse incentives/conflict of interests, (b) destabilising trading/investment strategies, (c) lack of disclosure/transparency and (d) concentrated versus fragmented ownership structures. The paper reviews the theoretical arguments and empirical evidence related to these four possible types of market failures, illustrating these with evidence drawn from the most recent corporate scandals. The last part of the paper is devoted to the policy responses both in the US and in Europe to prevent these failures.
Keywords: 330; Finanzmarkt; Wirtschaftsprüfung; Corporate Governance; Rechnungswesen; Glaubwürdigkeit; Welt; EU-Staaten